ANALISIS SEMIOTIKA ROLAND BARTHES PADA POSTER SERIAL DRAMA QUEEN OF TEARS - Dwi Pratiwi, Wulan; Sofiawati, Selvi; Umairoh, Faikoh (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2024)
Korean drama series are currently trending as one of the most anticipated shows, the enthusiasm of the audience is not only felt in their own country but also in various countries including Indonesia. Netflix is one of the digital-based streaming TVs that broadcasts quality films and drama series that are the attraction for viewers with monthly/annual subscription fees that do not hinder viewers from being able to choose quality shows and according to their interests. This study was conducted to analyze, explore the meanings behind the signs on the poster of the drama series queen of tears using Roland Barthes' semiotics. This study uses a qualitative approach with data collection carried out through observation techniques and literature studies. After the data is collected, it is analyzed by the researcher. The results of the study obtained from the visual elements on the poster of the series show the two main characters differently where the left side indicates loving each other while on the right side they sit far apart is the distance between them but still united. This poster has a unique theme to describe its story with a side comparison.